AL – Islam learning at SD Muhammadiyah 2 Sidoarjo during the Covid 19 Pandemic - Talitha Destiny Sasmithaningrum; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
After the World Health Organization (WHO) declared COVID-19 a global pandemic, several countries began to implement various policies and recommendations. This policy and recommendation is carried out because it is to break the chain and also reduce the spread of the covid 19 virus. For example, in Indonesia, the government makes a policy to move at home. There are so many activities that are carried out from home, for example learning from home, working from home (WFH) for teachers and office workers. The purpose of writing this research is to find out how the learning model that exists in schools during the current pandemic. And explained how the usual learning at SD Muhammadiyah 2 Sidoarjo was carried out during this covid-19 pandemic. The research method used is descriptive qualitative research. That is a study that understands the problem of using what media during the COVID-19 pandemic, the advantages and disadvantages of online learning, the ability of students to use technology and students' understanding of online learning. In the research process this time using interview and observation techniques during the research process. In this study, it is explained what kind of learning model carried out by SD Muhammadiyah 2 Sidoarjo, such as when the level of the COVID-19 pandemic was still high, schools carried out full online learning so that it could run effectively, efficiently, optimally and could take place well. The learning media used are multimedia-based in the form of whatsapp, zoom, google classroom. With this research, we know how to find strategies in distance learning during the covid 19 pandemic so that the teaching and learning process runs smoothly like face-to-face learning.